2014
DOI: 10.1007/s00330-014-3327-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast-Enhanced MR Imaging of Endometrial Cancer: Optimizing the Imaging Delay for Tumour-Myometrium Contrast

Abstract: • Recent advances have allowed for MR imaging of high temporal resolution. • Contrast-enhanced MR imaging is helpful for evaluation of endometrial cancer. • An imaging delay of 90 seconds may be optimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…On T2WI, endometrial cancer has the same or lower SI than the normal endometrium and stands out against low SI inner myometrium (junctional zone, JZ) (99, 100). On DCE-MRI, most tumors enhance homogenously, as well as slower and less intensely than the myometrium, with peak myometrial enhancement and maximal tumor-to-myometrium contrast occurring about 90–120 seconds after intravenous administration of contrast medium (101, 102). On DWI, tumor has high SI on high-b-value images and low SI on ADC maps relative to the myometrium (103106).…”
Section: Part V: Fertility-sparing Management Of Endometrial Cancermentioning
confidence: 99%
“…On T2WI, endometrial cancer has the same or lower SI than the normal endometrium and stands out against low SI inner myometrium (junctional zone, JZ) (99, 100). On DCE-MRI, most tumors enhance homogenously, as well as slower and less intensely than the myometrium, with peak myometrial enhancement and maximal tumor-to-myometrium contrast occurring about 90–120 seconds after intravenous administration of contrast medium (101, 102). On DWI, tumor has high SI on high-b-value images and low SI on ADC maps relative to the myometrium (103106).…”
Section: Part V: Fertility-sparing Management Of Endometrial Cancermentioning
confidence: 99%
“…Before May 2014, our institution conducted dynamic CE MRI as a standard part of preoperative MRI for endometrial cancer. Based on scienti c evidence [15], we adopted single-phase CE MRI instead of dynamic CE MRI in May 2014. We retrospectively searched our database for women who underwent single-phase CE MRI and surgically proven endometrial cancer, and the last 30 consecutive women were selected as the single-phase CE MRI group.…”
Section: Study Populationmentioning
confidence: 99%
“…T2-weighted imaging (T2WI), contrastenhanced imaging, and diffusion weighted imaging (DWI) are key MRI sequences to assess myometrial invasion of endometrial cancer. Of these, contrast-enhanced MRI (CE MRI) is mostly performed as hightemporal-resolution, dynamic CE MRI [13,8,[14][15][16][17]. However, high-spatial-resolution, single-phase CE MRI is also an option.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In its current guidelines, the European Society of Urogenital Radiology (ESUR) recommends dynamic contrast-enhanced (DCE) MRI for the staging of endometrial carcinomas and for facilitating patient selection before fertility-sparing management in organ-confined endometrial carcinoma and early stage cervical carcinoma that qualifies for trachelectomy (1,2). Numerous studies have shown that multiphasic contrast-enhanced MRI has high diagnostic accuracy for detecting deep myometrial invasion (MI) of endometrial carcinoma, an important prognostic factor that potentially influences not only treatment decisions, but also prognosis (3)(4)(5). Moreover, infiltrations of the bladder and rectal wall in advanced tumor stages can be seen better on contrast-enhanced sequences than on noncontrast-enhanced acquisitions (6).…”
Section: Introductionmentioning
confidence: 99%